Chromolaena odorata L. Leaf Extract Elevates Cytotoxicity of Doxorubicin on 4T1 Breast Cancer Cells - Putri, Amaliya Permata; Rahmawati, Desty Restia; Rahman, Faaza Aulia; Meiyanto, Edy; Ikawati, Muthi (Indonesian Society for Cancer Chemoprevention, 2023)
Chemotherapeutic agents for breast cancer such as doxorubicin can attack normal cells as the side effects. Chromolaena odorata L. and its chemical content, sinensetin, have potential anticancer and antioxidant properties. The objective of this research is to examine the anticancer properties of C. odorata leaves extract and sinensetin on 4T1 triple negative breast cancer (TNBC) cells combined with doxorubicin. The MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5 diphenyltetrazolium bromide) assay on 4T1 cells was used to determine the IC50 and the Combination Index (CI) of the two agents in combination. Washing out the treatment and determining the cells viability after a few days was done to evaluate the persistence of the effects to cancer cells. Chromolaena odorata extract (COE) obtained was proven to contain sinensetin which gave a positive signal on the chromatogram. COE and sinensetin were moderately cytotoxic to 4T1 cells with IC50 value of 53 μg/mL and 58 μM (21.6 μg/mL), respectively. Both compounds were synergist (CI<0.7) to strong synergist (CI<0.3) when combined with doxorubicin (IC50 90 nM = 0.05 μg/mL). COE and sinensetin exhibited moderate and not cytotoxic against Vero cells with IC50 values of 60 μg/mL and 243 μM (90.43 μg/mL), respectively. Both COE and sinensetin showed selectivity index values of >1 (1.13 and 4.19, respectively). Moreover, the cytotoxic effects of COE on 4T1 cells was persisted until 48 h after removing COE from the medium, indicating the tumor-suppression potency of COE. Our findings strengthen the scientific basis of C. odorata leaves extract to be developed as a co-chemotherapeutics agent for doxorubicin on TNBC.Keywords: Chromolaena odorata L., breast cancer cells, doxorubicin, co-chemotherapy, kidney cells.